KEMUNCULAN RAJA NANSARUNAI DALAM PUSARAN IKN - Hadi Miter; Kinurung Maleh; Sudianto (Jurnal Teologi Pambelum, 2023)
AbstractThe relocation of the Indonesian National Capital to East Kalimantan has proven to be a magnet for many groups to compete to show their existence in various aspects: socioeconomic, ecological, political, and cultural. A successful businessman in East Kalimantan, namely Abriantinus, brought his socio-cultural identity as a Ma'anyan Dayak and confirmed him as King Nansarunai in Betang Sanggu, South Barito. Nansarunai is a name full of history, meaning, and the traditional identity of the Ma’anyan people. With the title of King, Abriantinus hopes to be able to elevate the cultural values and potential of the Dayak people in the new National Capital. This confirmation received responses from various parties. The heads of the three Dayak Maanyan kadamangan agreed that the title of the king could be accepted if it had a socio-cultural nuance rather than being used for political and sovereign interests. The research method used in this paper is a qualitative one to describe each part of the data collected. This type of research is descriptive, with data collection methods including interviews, observation, and literature study. Keywords: Abriantinus, King Nansarunai, Dayak Ma'anyan, social identity, and social interaction. AbstrakPemindahan Ibu Kota Negara ke Kaltim terbukti menjadi magnet bagi banyak kalangan untuk berlomba menunjukkan eksistensinya dalam berbagai aspek: sosial ekonomi, ekologi, politik dan budaya. Seorang pengusaha sukses di Kalimantan Timur, yaitu Abriantinus membawa identitas sosial budayanya sebagai Dayak Ma'anyan dan mengukuhkannya sebagai Raja Nansarunai di Betang Sanggu - Barito Selatan. Nansarunai adalah nama yang sarat sejarah dan makna serta identitas tradisional masyarakat Maanyan. Dengan gelar Raja, Abriantinus berharap mampu mengangkat nilai budaya dan potensi masyarakat Dayak di Ibu Kota Negara yang baru. Konfirmasi ini mendapat tanggapan dari berbagai pihak. Kepala tiga kadamangan Dayak Maanyan berpandangan bahwa gelar raja bisa diterima asalkan bernuansa sosial budaya, bukan untuk kepentingan politik dan kedaulatan. Metode penelitian yang digunakan dalam penulisan ini adalah metode kualitatif untuk mendeskripsikan setiap bagian dari data yang dikumpulkan. Jenis penelitian ini adalah deskriptif dengan metode pengumpulan data melalui wawancara, observasi dan studi pustaka. Kata kunci: Abriantinus, Raja Nansarunai, Dayak Ma’anyan, Identitas Sosial dan Interaksi Sosial.